LANGUAGE OF THE BODY, VOICE OF RESISTANCE: FEMINIST APPROACHES TO TRANSLATING THE POETRY OF PAT PARKER AND AUDRE LORDE - Kočan, Kristina (Slavia Centralis, 2026)
This article addresses the translation of Black lesbian poetics in the works of Audre Lorde and Pat Parker, focusing on how embodied racial, sexual, and political subjectivity is negotiated in Slovene translations. Drawing on feminist, lesbian, and intersectional translation frameworks, it develops original readings of key poetic features—embodied Blackness, erotic embodiment, and anger as resistance—and shows how these demand translation strategies that exceed linguistic transfer and involve ethical engagement. Through selected poems, the article demonstrates how grammatical gender, metaphor, tone, and rhythm shape the visibility of marginalized voices in translation. Situating these cases within feminist macro- and micro-strategies, it proposes interventions such as supplementing, retranslation, and creative or neologistic solutions. The article argues that translating Lorde and Parker into Slovene constitutes an ethical and political act that expands the Slovene literary space for embodied and resistant Black lesbian poetics.
Keywords: translation; feminist translation strategies; contemporary American poetry; Black Poetry; Audre Lorde; Pat Parker